Chitosan and Chitosan Nanoparticles: Parameters Enhancing Antifungal Activity - Pawel Poznanski; Amir Hameed; Waclaw Orczyk (Molecules, 2023)
Chitosan (CS), a biopolymer derived from chitin, is known for strong antifungal activity while being biodegradable, biocompatible, and non-toxic. Because of its characteristic it has been widely used in control of fungal pathogens. Antifungal activity of chitosan can be further enhanced by obtaining chitosan nanoparticles (CSNPs). However, most of the experiments using CS and CSNPs as antifungal agents were performed under various conditions and using diverse CS batches of different characteristics and obtained from different sources. Therefore, it is essential to systematize the available information. This work contains a current review on how the CS parameters: molecular weight, degree of deacetylation, acetylation pattern and dispersity of these features shape its antifungal activity. It also considers how concentration and protonation (pH) of CS water solutions define final biological effect. Review explains in detail how CS parameters affect characteristics of CSNPs, particle size, zeta potential, and dispersities of both and determine antifungal activity. In addition to the parameters of CS and CSNPs, the review also discusses the possible characteristics of fungal cells that determine their susceptibility to the substances. The response of fungi to CS and CSNPs varies according to different fungal species and their stages of development. The precise knowledge of how CS and CSNP parameters affect specific fungal pathogens will help design and optimize environmentally friendly plant protection strategies against fungi.